Some studies of charge transfer complexes - Wright, J (1965)
The range of materials known as charge-transfer or molecular complexes has been extended to include compounds having metal complexes, with aromatic ligands, as electron donors. 8-hydroxyquinoline and its copperII, palladiumII and nickelII chelates were found to be suitable stable, planar donor molecules. They are conveniently soluble in solvents which also dissolve organic electron acceptor molecules. Solid complexes of these donors with thirteen electron acceptors have been prepared and analysed. Experiments testing the suitability of other metal complexes as donors are described, but none of the materials tested was satisfactory, with the exception of copper and palladium 5-methyl-8-hydroxyquinolinates. Attempts to prepare dichlorodicyanobenzoquinone complexes of 8-hydroxyquinoline or its nickel chelate, and the tetracyanoethylene/8-hydroxyquinoline complex, gave transient charge transfer interactions, followed by further reaction. Spectroscopic work on these systems is reported briefly, and suggests that electron distribution as well as ionization potential and electron affinity data are needed to explain the transition from complex formation to complete electron transfer and redox reactions. The solid complexes have been studied by x-ray crystallography, visible, ultraviolet and infra-red spectroscopy, electron spin resonance, and electrical conductivity measurements. Three-dimensional crystal structures of the palladium 8-hydroxy-quinolinate complexes with chloranil and tetracyanobenzene have been determined by the x-ray diffraction method. The multiple film Weissenberg technique was used to photograph 1880 and 1920 reflections, respectively, the intensities being estimated visually. A three-dimensional Fourier synthesis, phased on the palladium atom, located all atoms apart from hydrogens. The chloranil complex structure was refined using six cycles of a programme involving a block diagonal approximation to the normal least squares matrix, with anisotropic temperature factors and weighted data. The final R value was 0.108. The tetracyanobenzene complex structure was refined using two cycles of a full-matrix least squares programme, with isotropic temperature factors and unit weight for all data. The final R value was 0.102. These structures, and those of four more of the complexes, determined by other workers, are discussed, and show the following features: They contain stacks of alternate donor and acceptor molecules, in a plane-to-plane arrangement, the inter-planar spacing being close to the van der Waals distance of 3.40Å found in aromatic hydrocarbons. Molecules in adjacent stacks frequently form approximately planar sheets. Van der Waals attractions and repulsions frequently lead to the acceptor molecule being tilted with respect to the 8-hydroxyquinolinate plane. The Mulliken "Overlap and Orientation" principle is rarely obeyed, particularly if interactions between atoms of the acceptor and the metal atom are strong. The stoichiometries of the compounds depend on the possibility of specific interactions between atoms of the acceptor and the metal atom, the complexing strength of the acceptor molecule, and the relative lattice packing efficiencies of alternative stoichiometries. Apart from effects specifically due to the metal atoms, these structures are of the same type as those of organic molecular complexes Reflection spectra of the complexes show broad, intense bands in the visible region of the spectrum, not present in the spectra of the components. These are due to charge transfer from the filled x orbitals of the donor to the vacant x orbitals of the acceptor. Comparison of these bands with those of organic molecular complexes shows that the charge transfer transitions are of the same type as the latter. Spectra are therefore interpreted using the theories developed for organic complexes. Ionization potentials and orbital energies deduced from charge transfer spectra, using these theories, show that the linking together of two 6-hydroxyquinolinate groups through a metal atom raises the energy of the highest filled x orbital, to an extent proportional to the ease with charge transfer between the metal and ligand occurs. Thus, the order of donor power is low spin NiII > low spin PdII > CuII and 5-methyl-8-hydroxyquinolinates > 8-hydroxyquinolinates. Several of the electron acceptors used are new, and in these cases spectra of a selection of organic molecular complexes have also been recorded, and the electron affinities of the acceptors have been deduced. The order of electron acceptor power for these acceptors (including trinitrobenzene for comparison) is tetracyanobenzene ≃ dinitrobensfuroxan > nitrobenzodifuroxan > picryl azide ≃ dichloronitrobensfuroxan > benzotrifurazan ≃ benzotrifuroxan > trinitrobenzene. This series shows that electron withdrawing groups, such as the cyano or nitro groups, increase electron acceptor power, unless ateric factors prevent them from exerting their full influence by preventing conjugation with the rest of the molecule. Infra-red spectra of the complexes closely resemble the superimposed spectra of the component molecules, showing that the percentage of charge transfer character mixed into the ground states of the complexes is small. Small shifts of 20 cm.-1 or less in some of the bands of the complex are attributable to this small amount of charge transfer character in the ground state. Electron spin resonance spectra of single crystals of palladium 8-hydroxyquinolinate/chloranil doped with 0.1, 1.0 and 10 percent of the isostructural copper complex, have been recorded. These show four sets of lines, due to interaction of the impaired electron with the nuclear spin of copper (3/2), each set comprising five hyperfine lines, due to delocalisation of the electron onto the nitrogen atoms of the ligands. In the most dilute sample, the five hyperfine lines are each resolved into three extra-hyperfine lines, possibly due to further delocalisation onto the hydrogen atoms on the carbon atoms adjacent to the nitrogens. The line width increases more rapidly between 1 and 10 percent of copper complex present than between 0.1 and 1 percent. This is a consequence of the structure, in which each 8-hydroxyquinolinate molecule has ten near neighbours of the same type, and suggests that the copper complex molecules are distributed evenly in the lattice. A regular dependence of the shape and position of the spectrum on the orientation of the crystal with respect to the field was observed, but a more accurate means of orientating the crystal is required before these results can be interpreted with certainty. An apparatus capable of measuring the photoconductivity of single crystals with resistances of up to 1015Ω at different wavelengths at room temperature has been constructed and tested. All the complexes which could be obtained as large single crystals were examined for photoconductivity properties, and 8-hydroxyquinoline/tetracyanobenzene and copper and palladium 8-hydroxyquinolinate/chloranil complexes were found to photoconduct. The spectral response curves of photoconductivity show two regions of response related to the intermolecular charge transfer absorption band of the complex, one to high energy and the other to low energy of the absorption band. To elucidate the mechanism of photoconduction, a series of crystals containing from 0 to 30 percent of copper 8-hydroxyquinolinate/chloranil doped into the corresponding palladium complex was prepared. The copper content of these crystals was determined using the milliprobe x-ray fluorescence technique. The resistivities of the crystals vary considerably as the copper content changes. From these results, it has been deduced that the two regions of response are caused by different mechanisms. The high energy response is due to formation of highly energised ion pairs, produced by charge transfer from an excited donor molecule to an acceptor molecule, induced by light of energy corresponding to the region of overlap between inter- and intra- molecular charge transfer transitions. The low energy response is caused by the trapping of the negative charge of a normal ion pair, produced by the intermolecular charge transfer transition, leaving the positive hole free to migrate over a network of neighbouring donor molecules. The copper complex donors act as electron traps, and, at high copper concentrations, as positive hole traps. The possible relevance of these results to the mechanism of the primary quantum conversion act in photosynthesis is discussed briefly.